UPAYA MENINGKATKAN HASIL BELAJAR TENTANG SISTEM EKSRESI MANUSIA MELALUI MODEL THINK PAIR SHARE TERHADAP SISWA KELAS VIII - Nuraini, Novi Alfina; Hidayat, Saleh (Prosiding Temu Ilmiah Nasional Guru, 2023)
Refinement of the Think Pair Share learning model to help grade VIII students recognize the Elimination System material. A total of 30 students of grade VIII of SMP Budi Luhur Boarding School participated in this study. In the think-pair- share learning model, student learning outcomes were measured using board observation as a data collection tool. The think-pair-divide method used to prohibit material about the excretory system to students of class VIII SMP Budi Luhur proved to be able to improve learning outcomes. Only 30% of students achieved learning outcomes at the completion of Cycle I activities, but with the completion of Cycle II it increased to 70%. From this it can be concluded that the TPS learning model improves student learning outcomes.